GEMHEP multicenter quality control study of PCR detection of GB virus C/hepatitis G virus RNA in serum - Bogard, Marc; Buffet-Janvresse, Claudine; Cantaloube, Jean-François; Biagini, Philippe; Duverlie, Gilles; Castelain, Sandrine; Izopet, Jacques; Dubois, Martine; Defer, Christine; Lepot, Isabelle; Coste, Joliette; Marcellin, Patrick; et al. (Journal of clinical microbiology, 1997)
PCR is, to date, the only available tool for the detection of GB virus C (GBV-C) and hepatitis G virus (HGV) RNAs. Twenty-two French laboratories participated in a quality control study to assess the sensitivity and specificity of their procedures. The panel included 13 positive controls and 7 negative controls. The laboratories used either in-house PCR techniques adapted from the literature or partly standardized commercial tests. Three laboratories performed faultlessly with the entire panel. Most laboratories had excellent specificity (100% in 20 of 22 laboratories). Sensitivity was acceptable (85 to 100%) in 15 centers and insufficient (38 to 77%) in 7. As with nonstandardized in-house PCR, the commercial assays gave discrepant performances in different laboratories. These results suggest that laboratories willing to use PCR for detection of GBV-C/HGV RNA for research or diagnostic purposes should participate in multicenter quality control trials.